Impact of COVID-19 Pandemic on the Migrant Workers and Public Policy in Case of Malaysia & Indonesia - Karthikheyan, Dr. T. C.; Gopalan, Dr. K. R.; Marimuthu, Dr. U.; Dr. Bhoopathi Reddy B; Jessy K Jayanth (South Eastern European Journal of Public Health, 2024)
B The COVID-19 (Corona Virus Disease 2019) pandemic has changed the world altogether to a different plane. It has disrupted economy, health, family, society, etc. and there is no one left who has not been affected by it. Public Policy in case of migrant workers finds important place in this calculation. For, they play an important role in many of the economies, and still are the most vulnerable section of people who has been affected by the COVID-19 pandemic. Their problem emanates from various angles like that of being a legal or illegal (unaccounted) migrant worker, vulnerabilities emanating from lack of bargaining power with their employers and host nations, lack of safety working and hygienic living conditions, access to proper affordable health care facilities, etc. For the international migrant workers (who crosses border from home state to another state for purpose of employment or better economic aspirations), things have been really difficult in these pandemic times in terms of how they were treated by the authorities in the host countries and what kind of national public policy measures was taken to assure their physical health and mental wellbeing, engaging with them to assuage their psychological trauma caused due to various pressures and stress, economic condition, etc. Women migrant workers were more affected in way of losing their jobs, livelihood, family pressures and responsibilities. This paper looks into the effect of COVID-19 pandemic on the migrant workers, particularly with a focus on public policy measures taken in Malaysia and Indonesia, as these two nations contributes major chunk of migrant workers (inward and outward respectively) in the south-East Asian region. Apart from detailing the problems faced by the migrant workers during the pandemic times, this paper will dwell deep into the kinds of national public policy measures implemented towards the migrant workers as a response to the pandemic condition and its impact. In addition, this paper will also look into the role and policy of international organisations and NGOs towards the same. Apart from analyzing the problems and identifying the gaps in the approach of the respective governments, recommendations are also made to the public policy makers to improve the effect of their public policies and actions towards the migrant workers, on the basis of highlighting some good practices that are followed in other states.